Implementing Customer ‎ Relationship Management (CRM) in the Framework of Electronic- Government - Taher Roshandel Arbatani; Ata Ghaffari; Habib Ebrahimpour (Journal of Information Technology Management)
Electronic government is a new concept that governments according to level of development implement in different ways. Utilizing informational systems in business sections has created potential context for developing electronic government. Customer relationship ‎management (CRM) is an important system in management that helps to develop electronic government and promote citizenship-based in organizations. There are a few studies about implementing customer ‎ relationship management in framework of electronic government. However, this article surveys electronic government in technical approach and supply chain, then it develops graphical model for implementing customer ‎relationship management in framework of electronic government. This survey is done with Delphi method and presents electronic-government model based on customer ‎ relationship management. It is surveyed with modular factors, flexibility and criterion definition. Finally, it develops suggestions for implementing customer ‎ relationship management in framework of electronic- government.